Single Cobalt Atom Anchored Black Phosphorous Nanosheets as an Effective Cocatalyst Promotes Photocatalysis. Issue 15 (8th June 2020) - Ren, Xiaohui; Shi, Li; Li, Yunxiang; Song, Shuang; Wang, Qi; Luo, Shunqin; Ren, Long; Zhang, Hongwei; Izumi, Yasuo; Peng, Xinsheng; Philo, Davin; Ichihara, Fumihiko; et al.
Abstract: Exploring novel cocatalysts with sufficient active sites and rapid photogenerated carrier separation remains challenge for boosting photocatalytic reactions. Recently, two‐dimensional (2D) black phosphorus (BP) has been developed and recognized to be an ideal platform for anchoring metal ions through lone pair electrons. Herein, we propose a new structure that cobalt atomically dispersed on BP nanosheets (BP−Co), and apply it as cocatalyst for photocatalytic H2 evolution and CO2 reduction under visible light (>420 nm) irradiation. Both scanning transmission electron microscope and X‐ray absorption near edge structure verified the existence of phosphorous‐coordinated Co sites. The interaction between Co and P brings greatly improvement on photocatalytic activities, and 18‐fold enhancement can be achieved on CdS when taking BP−Co as a noble‐metal‐free cocatalyst for H2 evolution, which is higher than that of Pt under the same conditions. Besides, BP−Co can also be used as an effective cocatalyst to promote photocatalytic CO2 reduction in the presence of photosensitizer [Ru(2, 2'‐bipyridy)3 ]Cl2 with a CO evolution rate of 88.6 μmol h −1, superior to those obtained from the state‐of‐the‐art cocatalysts. It is anticipated that the current work might provide basic understanding as well as new opportunities on 2D BP nanosheets for versatile photocatalytic reactions. Abstract : Photocatalysis : A new structure that cobalt atomically dispersed on BP nanosheets (BP−Co) has been realized, and applied as a noble metal‐free cocatalyst for photocatalytic H2 evolution and CO2 reduction under visible light (>420 nm) irradiation. In this work, the photocatalytic reduction performance increased dramatically due to additional charge transfer channel and active sites derived from Co−P(O) interactions.